Implementation of Evidence-Based Nursing Practice: A Combination of Guided Imagery and PC6 Acupressure to Reduce Nausea in Patients Undergoing Chemotherapy - Eppy Setiyowati; Moh Sadli; Widayati Widayati; Mardliyah Mardliyah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Chemotherapy-Induced Nausea and Vomiting (CINV) is a common side effect in cancer patients undergoing chemotherapy. This condition can reduce quality of life and therapy compliance. Non-pharmacological approaches such as guided imagery and PC6 acupressure are alternative evidence-based interventions. To describe the implementation of Evidence-Based Nursing Practice (EBNP) in the form of a combination of guided imagery and PC6 acupressure and to evaluate changes in nausea levels in patients undergoing chemotherapy. EBNP implementation was carried out on 10 cancer patients undergoing chemotherapy at Dr. Mohammad Soewandhie General Hospital, Surabaya. The interventions provided were guided imagery for 10–15 minutes and PC6 acupressure for 2–3 minutes. The level of nausea was measured before and after the intervention using the INVR ( Index of Nausea, Vomiting, and Retching ) instrument. Data analysis used the Wilcoxon test with a significance level of α = 0.05. All respondents experienced a decrease in nausea scores after the intervention. A total of 5 (50%) respondents experienced a decrease in the nausea category, while 5 (50%) respondents remained in the same category even though the nausea score decreased. The results of the Wilcoxon test showed a p value = 0.025 (p < 0.05), which means there was a significant difference between before and after the intervention. The combination of guided imagery therapy and PC6 acupressure showed effectiveness in reducing nausea levels in chemotherapy patients.